MEMBACA FENOMENA PERDAGANGAN MANUSIA (HUMAN TRAFFICKING) DI INDONESIA DALAM TERANG KONSEP RELASI AKU-ENGKAU MARTIN BUBER - Yohanes D Naimnanu; Oktovianus Kosat; Dominikus Saku (IAIN SYEKH NUR JATI, 2023)
The research aims to examine the concept of human relations in Martin Buber's thought and seeks to read this concept against the phenomenon of human trafficking in Indonesia. The formulation of the questions in this study are; what is the concept of the I-thou relationship from Martib Buber's point of view? and how is this concept used to read (analyze, view) the phenomenon of human trafficking crimes in Indonesia? This paper is analyzed using the literature review method through literary sources such as books, journals and relevant articles. The results of the study found that Martin Buber divides human relations into two types, namely the I-it relationship and the I-thou relationship. Through the pattern of the